Entrepreneurial orientation in the hospitality industry: evidence from Tanzania. Issue 4 (6th March 2020) - Njoroge, Msafiri; Anderson, Wineaster; Mossberg, Lena; Mbura, Omari
Abstract : Purpose: The purpose of this study is to identify and validate indicators of entrepreneurial orientation (EO) in the hospitality industry, as well as to examine its dimensionality in the context of emerging economies with a specific focus on tourist hotels in Tanzania. Design/methodology/approach: The study uses a mixed-method approach for data collection and analysis. The qualitative study involved 20 in-depth interviews with hotel managers. Based on interview insights, indicators of EO were identified and applied in contextualizing the study and develop the survey questionnaires. The second phase, which was quantitative in nature involved a survey of hotels (n = 346) in the Coastal and Northern tourist circuits of Tanzania for validation and generalization. The exploratory and confirmatory factor analyses were used to analyze the quantitative data. Findings: EO in the studied context consists of proactive-risk-taking, innovativeness and competition approach. Hotels focus on proactive and risk-taking efforts concurrently, undertake wide-ranging acts; pursue bold and risk decisions in exploiting opportunities; being proactive on opportunity exploration but less emphasis on initiation speed on actions of competitors. Innovativeness focuses on providing quality services; standardization of services; product introduction; and technological advancements. Besides, the conventional dimensions, hotels use competition approach geared at extensive marketing; customer management; and flexibility in pricing based on competition. EO also exhibits multidimensionality with its dimensions exhibiting moderate-to-high correlations and with acceptable discriminant validity. Practical implications: The study's findings imply that EO and its respective indicators confirmed in western contexts are not necessarily a perfect reflection and applicable in the hospitality industry in emerging economies like Tanzania. Hospitality firms must be vigilant with contextual characteristics – economically, socially and culturally shaping entrepreneurial opportunities. Originality/value: This study identifies and validates indicators of EO in the hospitality industry in emerging economies. Moreover, the study adds to the body of knowledge that EO in this context is also multidimensional in nature.